Garuda platform: re-imagining connectivity in medicine - Ghosh, Samik (Henry Stewart Talks, 2018)
Computational landscape in systems biology and bioinformatics, The Garuda platform: ability to connect, discover and inter-operate diverse databases, tools and techniques for analysis of data and visualization, High Dimensional (HD) data and analytics, Building custom pipelines for data analysis, Using Garuda in biomedical & healthcare research